Effect of the inclusion of Azolla filiculoides meal on the growth and survival of red tilapia small fish (Oreochromis mossambicus x O. niloticus) - Méndez-Martínez, Y.; Pérez, Y.; Verdecia, D. M.; Cortés-Jacinto, E.; Cevallos, O. F.; Romero, O. (Cuban Journal of Agricultural Science, 2019)
An experiment in Acuipaso Station, Granma province, Cuba was carried out to evaluate the effect on growth and survival indicators of inclusion levels (0, 10, 20 and 30 %) of water fern meal (Azolla filiculoides) in diets for red tilapia hybrid small fish (Oreochromis mossambicus x O. niloticus). A completely randomized design with four treatments and three repetitions was used; 120 small fish of 26 days of age were used, which were distributed in four groups of 30, ten small fish per tank (each tank represented a repetition). The chemical composition of meal was determined, and the variables: survival, weight and its increase, average gain and feed conversion factor were studied. The simple classification variance analysis was performed on the data obtained and it the Duncan test was used to compare the means. The chemical composition reported percentages of CP (20.74), CF (19.34) and adequate amino acid balance (1.40, 2.30, 2.65 and 3.14 % of methionine, arginine, lysine and valine, respectively); the oxygen, temperature and pH of the water (5.34 mg/L, 24.33°C and 8.02) were maintained at the optimum average value for this species. For the indicators of growth and survival there were significant differences (p <0.05) between all the treatments, except for the control and 10 % with results of 6.556g, 7.793 g/day, 1.85 g/g, 0.55 and 7.266 cm , for the final live weight, ADG, conversion, food efficiency and final length, respectively. It was concluded that Azolla filiculoides have an adequate chemical and amino acid composition so that it could be used in the feeding of red tilapia small fish, with 10 % of inclusion in the diet, results in accordance with the control diet were obtained in the productive indicators, without affecting the water quality. Key words: Azolla meal, red tilapia, average daily gain, conversion and food efficiency